Solvent-free glycerol transesterification with propylene carbonate to glycerol carbonate over a solid base catalyst - Kondawar, Sharda; Rode, Chandrashekhar (Energy & Fuels, 2017)
Glycerol transesterification using propylene carbonate (PC) to glycerol carbonate.(GC) could be efficiently performed under solvent-free 'conditions 'wing solid base as catalysts involving non-noble metal oxide in combination with hydrotalcites (HTs). Among all of the catalysts studied for transesterification, the best result was obtained over a calcium-doped hyclrotalcite (Ca-FIT) catalyst, giving 84% conversion of glycerol and almost complete. GC selectivity. The crystal structure of HT was modified by incorporation of Ca and La into FIT, as revealed by X-ray diffraction studies. The temperature-programmed desorption of carbon dioxide study confirmed the presence of the highest basic site density in terms of 1.94 mmol of CO2 desorbed/g of catalyst, responsible for its higher transesterification efficiency of the Ca-HT catalyst. The Fourier transform infrared spectroscopy study showed peaks at 3036 and 3042 cm(-1) for Ca -HT and lanthanum-doped hydrotalcite (La -HT), respectively, confirming the presence of hydrogen bonding between water and interlayer carbonate anions responsible for abstracting proton from the primary hydroxyl group of glycerol to attack over carbonyl carbon of PC. The presence of intercalated carbonate ions is also confirmed by the Raman study, in both PIT and ca-HT catalysts and even after use of the Ca HT catalyst. The thermogravimetry-differential thermal analysis study evidenced the higher thermal stability of the Ca -HT (T-4 = 765 degrees C) catalyst than that of parent HT with a Mg/Al ratio of 3:1 (T4 = 630 degrees C). Various process conditions, such as the temperature, molar ratio of glycerol/PC, and catalyst loading, significantly influenced conversion and selectivity of glycerol: and GC, Tespectively.

Crystalline LaCoO3 perovskite as a novel catalyst for glycerol transesterification - Phadtare, Deepshree; Kondawar, Sharda; Athawale, Anjali; Rode, Chandrashekhar (Molecular Catalysis, 2019)
LaCoO3 perovskite was synthesized using sol-gel method by nitrate and acetate precursors of La and Co with varying molar ratios of La and Co (1:1, 1:2 and 2:1). This was found to be an unique strategy to obtain highly crystalline LaCoO3 perovskite material without using any chelating agent. The variation of precursors was found to influence their crystallinity however, variation in molar ratio in the range of 0.5-2, did not affect the formation of perovskite framework. The formation of pure perovskite phase (around or > 80%) could be achieved by combination of acetate and nitrate precursors while, the combination of acetate- acetate or nitrate- nitrate precursors resulted in low phase purity for the perovskite due to the formation of secondary phases like La2O3 and Co3O4. Very interestingly, such combination of perovskite and pure oxide phases contributed to enhancement of basic sites which catalyzed the glycerol transestrifiaction with DMC (dimethyl carbonate) to GC (glycerol carbonate) and GD (glycidol). Among all the catalysts studied, NAP-2 showed highest efficiency in terms of 98% glycerol conversion and 77% GC and 22% GD selectivities. The highlight of this work is that first step glycerol transesterification with DMC required basic sites of either metal oxide or perovskite but for cascade reaction involving decarboxylation required both metal oxide as well as LaCoO3 perovskite phase.

Role of preparation parameters of Cu-Zn mixed oxide catalyst in solvent free glycerol carbonylation with urea - Charate, Shrinivas; Shinde, Suhas; Kondawar, Sharda; Desai, Uday; Wadgaonkar, Prakash; Rode, Chandrashekhar (Journal of the Indian Chemical Society, 2021)
Solvent-free carbonylation of glycerol with urea to glycerol carbonate (GC) was achieved over heterogeneous Cu-Zn mixed oxide catalyst. Cu-Zn catalysts with different ratios of Cu:Zn were prepared using co-precipitation (CP) and oxalate gel (OG) methods. As compared to CuO-ZnO(2:1) catalyst prepared by oxalate gel (OG) method, much higher conversion of glycerol and highest selectivity towards glycerol carbonate (GC) was achieved with CuO-ZnO_CP(2:1) catalyst. Physicochemical properties of prepared catalysts were investigated by using XRD, FT-IR, BET, TPD of CO2 and NH3 and TEM techniques. The effect of stoichiometric ratio of Cu/Zn, calcination temperature of CuO-ZnO catalysts and effect of reaction parameters such as molar ratio of substrates, time and temperature on glycerol conversion to GC were critically studied. Cu/Zn of 2:1 ratio, glycerol-urea 1:1 molar ratio, 145 degrees C reaction temperatures were found to be optimized reaction conditions to achieve highest glycerol conversion of 86% and complete selectivity towards GC. The continuous expel of NH 3 from reaction the mixture avoided formation of ammonia complex with CuO-ZnO catalyst. As a result of this, CuO-ZnO catalyst could be recycled up to three times without losing its initial activity.
Keywords: Co-precipitation (CP); Glycerol; Glycerol carbonate; Oxalate gel (OG)

Ionic liquids for the sustainable transformation of levulinic acid to gamma-valerolactone (GVL) - Kondawar, Sharda; Rode, Chandrashekhar (Current Opinion in Green and Sustainable Chemistry, 2022)
This short review is focused on recent findings on the role of ionic liquids (ILs) in catalysing the hydrogenation of levulinic acid (LA) to gamma valerolactone (GVL), which is a cascade reaction involving more than one type of reaction. A brief introduction on green aspects of IL as a catalyst followed by various types of ILs being used for hydrogenation of LA to GVL are discussed. The unique characteristics of ILs responsible for hydrogenation reaction are also explained along with the current and upcoming scenario of IL catalysed hydrogenation of LA to GVL.
Keywords: Biomass; Gamma valerolactone; Hydrogenation; Ionic liquid; levulinic acid